Assessment Level of Knowledge about Supplementary Polio Immunization in Mothers Presenting to Pediatric Population - Waheed Ullah, Sara Jamil Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Humans are the only known reservoir of polio virus. Polio virus infection in humans can cause a crippling paralysis in a fraction of the infected patients. Due to permanent nature of the paralysis, low mutation rate of the virus, restriction of polio virus to human hosts and overall feasibility of polio eradication, the polio virus became the target of aggressive vaccination campaigns via supplemental polio immunization (SPI) across the world for more than two decades. To determine the level of knowledge about supplementary polio immunization in mothers presenting to pediatric Population. Materials and Methods: This study was conducted in the Pediatric Department, OPD, District General hospital Timergara from 29-04-2021 to 29-7-2022. Through a descriptive, cross-sectional study design, 216 mothers of children aged 0-5 years, accompanying their children to the pediatric OPD, were included in the study through a consecutive manner and interviewed using a structured questionnaire. Results: In this study 216 mothers were included. Mean age of the mothers was 30.97 years. Most mothers had average level of knowledge (48.6%) while 30.6% had poor level of knowledge regarding supplementary polio immunization. Most common religion was Islam (96.3%). Illiteracy was the most common educational status (32.9%) followed by secondary (22.7%) and primary (19.4%) education. Majority (58.8%) of mothers were housewives. Pearson Chi Square test for Level of Knowledge wise stratification of Educational Status of the mother gave a value of c2=45.793 and was significant at p<0.05. Level of Knowledge wise stratification of Religion of the mother had 9 cells (75%) with expected count less than 5. Level of Knowledge wise stratification of Occupational status of the mother had c2=10.148 with p=0.11(i.e.>0.05). Finally, the Level of Knowledge wise stratification of Age groups of mothers had c2=2.87 with p=0.94(i.e. >0.05). Conclusion: Level of Knowledge of mothers regarding supplementary polio immunization is significantly associated with maternal educational status Keywords: Polio, supplementary polio immunization, polio drops